Cleaning ability of toothbrush with or without the use of dentifrice on debris and plaque removal in hostel inmates aged 20-24 years - Sachin Chand; Jitender Solanki (Wolters Kluwer Medknow Publications, 2014)
Objectives: The aim was to find the cleaning ability of the toothbrush with or without the use of dentifrice in removal of debris and plaque in hostel inmates aged 20-24 years. Materials and Methods: A randomized clinical trial was carried out on 30 undergraduate students of K.D. Dental College and Hospital. The debris and plaque scores were recorded using debris index-simplified and plaque index respectively. The subjects were divided into three groups. After recording the baseline scores, the study groups were instructed to follow the modified bass method for the period of 10 days and then follow-up scores were recorded. Paired 't'- test and one-way ANOVA test was used to compare the mean baseline and mean follow-up scores. Results: The difference in mean debris scores at baseline and follow-up for Group II (P = 0.000) and Group III (P = 0.005) was found to be statistically significant. However, for Group I (P = 0.153), this difference was not significant. The difference in mean plaque scores at baseline and follow-up in all the three groups was statistically significant. When the mean differences in debris and plaque scores of the three groups were compared, it was found to be statistically significant for Group I and Group II and Group I and Group III, however, it was not significant for Groups II and III. Conclusion: The present study showed that the cleaning ability of the toothbrush with dentifrice was more effective in the removal of debris and plaque than the cleaning ability of the toothbrush without dentifrice.